Síntese e avaliação de um líquido iónico alcalino na produção de biodiesel - Lima, Ana Carolina Coelho (2022)
Biodiesel is an attractive biofuel to overcome energy depletion from fossil fuels since it has similar properties to diesel and exhibit biodegradability, non-toxicity and low carbon content. Currently, the production of biodiesel is done by the conversion of edible oils containing triglycerides through a transesterification reaction. However, concerns related to first-generation biodiesel such as the high cost of these oils, the competition with food markets, and the possibility of soil degradation made the use of waste oils in biodiesel production a possibility. These oils are considered a promising alternative in biodiesel synthesis, due to their low cost, high availability and arise as possible alternatives to overcome the disadvantages of the traditional production processes. Therefore, this study focuses on the research of producing biodiesel in a more sustainable way, i.e., the production of biodiesel from waste oils and the application of an ionic liquid (IL) as catalyst. The interest in IL is related to their near-zero vapor pressure and other properties such as their low volatility, high thermal and chemical stability, solvent properties and the possibility to be recovered and reused in new reaction cycles. In this research, the bis-(3-methyl-1-imidazolium)-ethylene dihydroxide (IMC2OH) IL was synthesized and characterized, showing good catalytic character for the transesterification of sunflower oil samples. Thus, the IL will be applied in the transesterification of waste cooking oils, and the effects of different reaction conditions on the preparation of biodiesel, such as reaction time, reaction temperature, alcohol/oil molar ratio and catalyst dosage, will be assessed.